Management of cysto-biliary communication in hydatid cyst of liver - A Bhattarai (Society of Surgeons of Nepal, 2016)
Introduction: Biliary communication of hepatic hydatosis is one of the important complications. It may be minor or major communication. Minor communication is usually diagnosed during operation by the presence of bile stained hydatid fluid on aspiration or bile leak during surgery. However, in major communication, patients present with obstructive jaundice, abdominal pain and cholangitis. Surgical management of major communication is difficult and is associated with high morbidity and mortality.